Sex‐related differences of clinical features in hidradenitis suppurativa: analysis of an Italian‐based cohort. (28th December 2018) - Bianchi, L.; Caposiena Caro, R. D.; Ganzetti, G.; Molinelli, E.; Dini, V.; Oranges, T.; Romanelli, M.; Fabbrocini, G.; Monfrecola, G.; Napolitano, M.; Egan, C. G.; Musumeci, M. L.; et al.
Summary: The clinical characteristics associated with hidradenitis suppurativa (HS) severity are poorly understood. In this study, 124 patients with HS from 6 Italian dermatology centres participated in this study. Disease severity was assessed using the Hidradenitis Suppurativa Physician's Global Assessment score (HS‐PGA) and Hurley score. The impact of clinical characteristics on disease severity was assessed by logistic regression. Clinical characteristics were similar between men ( n = 53) and women ( n = 71). Disease severity was also similar; 75% of the patients had Hurley stage II or III disease, and > 60% had moderate, severe or very severe HS as judged by HS‐PGA. Lesions were more frequent in the gluteal region in men (32.3% in men vs. 8.7% in women, P < 0.001) and more frequent on the breast in women (16.3% in women vs. 4.6% in men, P = 0.02). Obesity was associated with increased disease severity as measured by HS‐PGA (OR: 3.28, 95% CI 1.55–6.95, P < 0.01) and Hurley classification (OR: 3.22, 95% CI 1.34–7.31, P < 0.01). Although severity of HS is similar between the sexes, the localization of lesions is different.